An Analysis of the Structure and Pragmatic Functions of Imperative Sentences in the Arabic Dialogue of the Animated Series Mansour (Episode خندق مريانا) - Nursukma Suri; Rima Mella; Khusnul Fatimah; Aisyah Natama Siregar (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to analyze the structure and function of imperative sentences in the dialogue of the animated series Mansour, episode خندق مريانا, from the perspective of Arabic linguistics. The research employs a descriptive qualitative method using documentation and discourse analysis techniques to examine Arabic utterances in the selected episode. The analysis focuses on the morphological form of fi’il amr, other imperative constructions that convey directive meaning, and their pragmatic functions in character interactions. The findings reveal that the dominant imperative form is fi’il amr, which morphologically conforms to standard Arabic grammatical rules in both singular and plural forms. In addition, the dialogue presents variations of imperative strategies, including hortative constructions and the use of colloquial particles that reinforce urgency and encouragement. Pragmatically, imperative sentences in the dialogue function not only as direct commands but also as warnings, technical instructions, invitations, and motivational encouragements. These functions are strongly influenced by situational context, interpersonal relationships among characters, and the level of urgency within the narrative structure. This study emphasizes that the analysis of imperative sentences in dialogic discourse must integrate grammatical structure and pragmatic function in order to achieve a comprehensive understanding of communicative strategies in Arabic.